La variation toponymique dans l'oraliture comme pratique infrapolitique : études de cas à Uchon et Paris - Jean-Baptiste Bing (EchoGéo)
his article sets out to show how oraliture by perpetuating the topicality of toponymic variation, constitutes a weapon of resistance and encapacitation in the realm of 'infrapolitics'. To do this, it focuses on two case studies: the microtoponymy applied on a daily basis by the inhabitants of the village of Uchon (Saône-et-Loire) and transmitted via narratives during commented tours; the odonymy of two Paris streets, transmitted via two narratives. After presenting the case studies and the corpus, the first part sets out some epistemological and methodological considerations on these, the way in which they are treated and the limits of the results that can be drawn from them. The second part then shows how tales, legends and oral narratives help to maintain a departure from the norm and standardisation and enrich everyday reality. Finally, the third section looks at the power of oral narratives to encapacitate a subaltern group in a power struggle. The article concludes with the importance of the variant in oraliture as an interstice where infrapolitical resistance can be imagined and embodied, transcending the differences in context between a metropolis and a hyperrural village.